Physico-chemical and biological characterization of soils from selected farmlands around three mining sites in Phalaborwa, Limpopo Province - Ramahlo, Masetle Nelson (University of Limpopo (Turfloop Campus), 2013)
The study was conducted to assess the impact of mining activities on selected soil physical, chemical and microbial properties on farmlands around three selected mining sites. Nine soil samples were collected from each of the following farms : Hans Merensky, Mogoboya and Leon Tom, Foskor Mine and JCI mining sites, respectively. Additional nine soil samples were collected from non-polluted Waterbok farm that serves as a control for the purpose of comparison. The samples were taken at 0–15, 15–30, 30–45 cm depths at three sampling points on each farm for physical, chemical and biological studies. However, soil samples collected for microbial (fungi, bacteria and actinomycetes) counts were surface (0–15 cm) soil samples. Soil chemical properties determined include pHw, electrical conductivity (ECe), exchangeable acidity (EA), organic carbon, available phosphorous, exchangeable cations as well as heavy metal (i.e. Mn, Zn, Cu, Pb, Cd, As and Sb) concentrations. The physical parameters determined include texture (sand, silt and clay) as well as bulk density. Soil pHw and ECe values decreased with depth; and ranged from 6.94 to 6.50 and from 12.24 to 10.76 mS cm-1, respectively. Exchangeable acidity showed a gradual increase with depth and ranged from 0.72 to 0.80 cmol(+)(kg), while percent organic carbon decreased with depth ranging from 1.41 to 2.19 %. Exchangeable cations, particularly K and Mg increased with depth while Ca decreased marginally with soil depth. Available phosphorous content decreased following increases in distance from the pollution source while heavy met.al contamination decreased with soil depth but increased further away from the pollution source. Significantly high loads of Pb, As and Sb were recorded at all depths on the three farms around the mining sites, which were largely responsible for the pollution but worse on the Leon Tom farm; with Pb constituting the greatest pollutant. The concentration of extractable heavy metals in the studied areas was in the order: As >Sb>Pb>Zn>Cu >Mn >Cd. Cadmium level appeared generally very low in all samples while elevated levels of Mn, Cu and Zn were detected at all depths in the polluted soils.Significant differences in microbial levels were detected at the various sampling points. The highest count of 3.82 and 6.20 CFU g-1 for fungi and actinomycete, respectively were both from the Leon Tom farm, while 6.46 CFU g-1 counts for bacteria was obtained from Mogoboya farm. Interestingly, fungal and actinomycetes activities were more sensitive to heavy metal contamination than bacteria that were significantly increased following soil pollution.
Thesis (M.Sc. (Soil Science)) --University of Limpopo, 2013
Keywords: Mining; Heavy metals; Soil microbes; Soil fertility; Soil pollution; 631.46; Soil pollution -- South Africa; Mineral industries -- Environmental aspects